Pengembangan Model Gerak Lokomotor dan Manipulatif melalui Sirkuit Traning Permainan di SD Negeri 01 Sima Kabupaten Pemalang - Zuhri, Mukhamad Akmal; Abdulaziz, Moch. Fahmi (YASIN, 2025)
This research aims to develop a game circuit training product as a solution to enhance students' interest and enjoyment in physical education learning. This initiative is motivated by the lack of enthusiasm among students in participating in lessons, which is attributed to the delivery of material that is less engaging and monotonous. The research was conducted at SD Negeri 01 Sima, Pemalang Regency, utilizing the Research and Development (R&D) method based on the Borg & Gall model. This research methodology aims to produce a specific product as an innovation to address existing problems. The steps taken in this research include (1) initial information gathering, (2) planning, (3) initial product creation, (4) expert validation, (5) product revision, (6) small-scale trials, (7) product revision, (8) large-scale trials, and (9) final product. The validation results from game and learning experts indicate that this model is highly feasible, with an average validation score of 3.44 from game experts and 3.24 from learning experts, both falling into the category of highly feasible. Furthermore, small-scale field trials at SD Negeri 01 Sima showed an average feasibility score of 59% across psychomotor, cognitive, and affective aspects. Meanwhile, large-scale trials yielded an average score of 80%, indicating that the game circuit training development model is effective in physical education learning for enhancing students' physical abilities, particularly agility and endurance. The game circuit training is deemed effective and suitable as an innovative method to improve the quality of physical education learning in elementary schools.